On the contextual nature of sex-related biases in pain judgments: The effects of pain duration, patient's anxiety symptoms and judge's sex. - Bernardes, S.F.; Lima, M. L. (European Journal of Pain, 2011)
Although women report feeling more pain than men their pain is often under-valued as compared to men's pain. We argue that such biases are not universal, being either enhanced or suppressed by context-related variables pertaining to the situation, the patient and the perceiver. Consequently, we aimed at understanding the effects of pain duration, patient's distress and the judge's sex on sex-related biases in pain judgements. Two-hundred and five nursing students (44.9% male) participated in a between-subjects design, 2 (pain duration) x 2 (patient's distress) x 2 (patient's sex) x 2 (participant's sex). Participants read a vignette depicting a man/woman going into an Emergency Room complaining of low-back pain, that he/she had had for 3 days/years, with/without signs of distress. Afterwards, participants judged the: (1) clinical severity/urgency; (2) pain credibility; and (3) pain disability. Findings showed that sex-related biases were only evident when pain was acute or expressed without distress. In these cases, the woman's clinical situation was perceived as less severe/urgent and her pain as less credible as compared to the man's. Moreover, only the judgments on the woman's pain were moderated by such contextual variables. Finally, male students were more biased than females. Implications for gender equality in pain treatments are drawn.